Pengaruh Kepemimpinan Transformasional dan Motivasi Ekstrinsik terhadap Kinerja Karyawan: Studi Pada Salah Satu Perusahaan Garmen di Kota Bandung - Ira Rahayu Tarwiyah; Nenny Rinawati; Retno Resawati; Adhie Fasha Nurhadian (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2021)
This research was carried based on the problems and the critical role of transformational leadership and extrinsic motivation in improving employee performance. To determine the effect of transformational leadership and extrinsic motivation on employee performance, the researchers conducted a survey on one of the garment companies in the city of Bandung with a simple random sampling technique of 67 employees. This study uses path analysis techniques to calculate the magnitude of the influence of transformational leadership and extrinsic motivation on employee performance either partially or simultaneously. The results showed that the real influence of transformational leadership was 47.4%. In comparison, the total effect of extrinsic motivation was 25.0%, so that the total effect was 72.4% with an epsilon of 27.6%, which was another factor not investigated.